Assessment of the Efficiency of Preventive Measures Undertaken by the Police in Poland. - Gwardyński, Robert; Kaczmarczyk, Barbara (Scientific Journal of Bielsko-Biala School of Finance and Law, 2019)
The Police are a uniformed formation intended to ensure security and public order. The formation plays an auxiliary role in relation to the society. The Police carries out assigned tasks of preventive, criminal and investigative nature. The purpose of this study is to assess the utilitarian effectiveness of the preventive anti-crime measures of the Polish Police forces. In order to achieve this goal, the authors used the method of examining relevant documents, statistics and literature. The main source of information were statistical data made publically available by the Polish Police and communications from surveys carried out by the Public Opinion Research Centre (CBOS). The period under examination included the years 2014-2017.